Effectiveness of Interactive Learning Videos Based on Problem-Based Learning to Increase Student Motivation and Critical Thinking Skills - Ulfaa, Irma; Lisdiana, Lisdiana; Saptono, Sigit (Unnes Science Education Journal, 2025)
The purpose of the study was to determine the effectiveness of the product to improve student motivation and critical thinking skill. The research employs a quantitative research method, involving expert validation, small group trials, and field implementation with students at the MTs level. The results of the validation process indicate that the videos are highly valid, achieving a validity score of 93%, demonstrating alignment with the curriculum, appropriate material presentation, and user-friendly language. Effectiveness testing using N-Gain analysis shows a significant improvement in student motivation and critical thinking skills after us ing the videos compared to conventional methods. Independent Sample T-Test results further confirm the significant positive impact of the videos on learning outcomes. Student responses indicate that the videos are engaging, interactive, and supportive of independent learning. This study concludes that interactive learning videos based on PBL are effective educational tools for enhancing stu dents’ understanding of complex topics, such as the body’s defense system, while fostering critical thinking and motivation. The findings highlight the potential of integrating technology-based media in classroom learning to achieve better edu cational outcomes.